2013
DOI: 10.1038/bjc.2013.564
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-guide risk prediction of hepatocellular carcinoma development in chronic hepatitis C patients after interferon-based therapy

Abstract: Background:Interferon (IFN)-based therapies could eradicate hepatitis C (HCV) and reduce the risk of hepatocellular carcinoma (HCC). However, HCC could still happen after sustained virological response (SVR). We aimed to develop a simple scoring system to predict the risk of HCC development among HCV patients after antiviral therapies.Methods:From 1999 to 2009, 1879 patients with biopsy-proven HCV infection treated with IFN-based therapies were analyzed.Results:Multivariable analysis showed old age (adjusted H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 37 publications
0
38
1
Order By: Relevance
“…The AUC was very similar in the derivation and validation cohort groups, 0.981 (95% CI=0.952‐1.00) and 0.979 (95% CI=0.948‐1.00), which represents the accuracy of the prediction model. Various score models in other types of hepatitis (B and C) have been developed for predicting the probability of disease and adverse events associated with it …”
Section: Discussionmentioning
confidence: 99%
“…The AUC was very similar in the derivation and validation cohort groups, 0.981 (95% CI=0.952‐1.00) and 0.979 (95% CI=0.948‐1.00), which represents the accuracy of the prediction model. Various score models in other types of hepatitis (B and C) have been developed for predicting the probability of disease and adverse events associated with it …”
Section: Discussionmentioning
confidence: 99%
“…A number of studies [2][3][4][5][6] have already reported the association between HCC development and age, sex, and AFP level. Although each parameter might be a predictive marker of HCC alone, the new scoring system (VFMAP) established in the present study includes all of these parameters and may therefore more accurately predict the risk of developing HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic liver disease, including that due to persistent infection with hepatitis B (HBV) and hepatitis C (HCV), is a risk factor for the development of HCC [2]. In addition, several factors such as high age, male sex, high a-fetoprotein (AFP) levels, and heavy drinking have been reported to increase the risk of developing HCC in patients with chronic liver disease [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Among HCV-infected individuals, risk factors for HCC include male sex, genotype 3 infection 11 , co-infection with HBV or HIV, diabetes, obesity, and high level of alcohol consumption. 12 Hispanics with HCV are at a significantly higher risk, whereas African Americans are at a considerably lower risk, of developing cirrhosis and HCC than non-Hispanic whites. HCV viremia of any level is a strong risk factor for HCC compared to no viremia.…”
Section: Identification Of At-risk Patients Based On Epidemiology Fimentioning
confidence: 95%